Adherence to the Mediterranean diet was positively associated with micronutrient adequacy and negatively associated with dietary energy density among adolescents. Issue 1 (13th November 2018) - Peng, W.; Berry, E. M.; Goldsmith, R.
Abstract: Background: The possible associations between adherence to the Mediterranean diet and micronutrient and energy intakes are unknown among Israeli adolescents. Methods: A cross‐sectional, nationally representative, school‐based study was conducted in Israeli adolescents. Schoolchildren ( n  = 5005), aged 11–18 years, who completed a food frequency questionnaire and had complete data to compose a 14‐item modified KIDMED score were included. Results: The nutrient intakes for all the micronutrients showed a significant monotonic increase in the poor, average and good KIDMED groups (all P  <   0.001). The same monotonic increasing was also shown in nutrient densities for most micronutrients (for calcium, magnesium, potassium, copper, vitamin A, vitamin E, vitamin C, thiamin, riboflavin, vitamin B6, folate in both genders, additionally for phosphorus in girls) (all P  <   0.05). A positive association was shown between the percentages of students with adequate intakes (AIs) or recommended dietary allowances (RDAs) in micronutrients and modified KIDMED scores. The positive association also existed between the number of micronutrients with AIs or RDAs and modified KIDMED scores ( r  = 0.495 and 0.501, P  <   0.001) for boys and girls, respectively. By contrast, dietary energy density (calibrated by 1000 kcal) was negatively linearly associated with modified KIDMED scores, and a significant monotonic decrease in energy density was shown among the poor, average and good KIDMED groups (all P  <   0.001). Conclusions: The modified KIDMED score was positively associated with better micronutrient profile and negatively associated with dietary energy density in Israeli adolescents, indicating that the KIDMED index is a useful tool for combating the malnutrition of micronutrient deficiency and overweight/obesity.